Comparing the Quality of Life of Patients With Hemophilia and Juvenile Idiopathic Arthritis in Which Chronic Arthropathy Is a Common Complication. Issue 8 (November 2015) - Oymak, Yesim; Kaygusuz, Arife; Turedi, Aysen; Yaman, Yöntem; Eser, Erhan; Cubukcu, Duygu; Vergin, Canan
Abstract : Introduction: Hemophilia is a genetic disorder in which recurrent joint bleeding causes arthropathy. Inflammation and degeneration play roles in the pathogenesis of hemophilic arthropathy. Patients with juvenile idiopathic arthritis (JIA) experience a similar inflammatory degenerative joint disease. A comparison of different patients with common pathogenetic features may identify unique features helpful in terms of the follow-up. Aim: We compared the quality of life (QoL) of patients with hemophilia and JIA, and healthy controls, using a generic QoL scale, Kidscreen and Disabkids Questionnaires (KINDL). Differences among groups were evaluated in terms of sociodemographic characteristics and clinical parameters affecting the QoL. Methods: We included 33 hemophilia patients, 19 JIA patients, and 32 healthy individuals aged 4 to 18 years. Sociodemographic characteristics (the age, the maternal educational status, the place of residence, the size of the household, the household income, divorced parents) were noted, and the KINDL was administered to all participants. Clinical parameters associated with arthropathy (the functional independence score [FISH], the hemophilia joint health score [HJHS], the arthropathic joint count, and the painful joint count) were documented. Differences in frequencies and medians among the groups were evaluated using the χ 2, the Mann-Whitney U, and the Kruskal-Wallis tests. Results: All KINDL dimensions were above 50, reflecting "good conditions" in the 2 patient groups. No difference between patients with hemophilia and JIA was evident in terms of the clinical parameters of FISH, the HJHS, or the arthropathic or painful joint counts ( P >0.05). Sociodemographically, only the frequency of literate mothers was lower in patients with hemophilia than in those with JIA and healthy controls ( P =0.03). Patients with JIA scored more higher on the KINDL dimension of chronic illness than those with hemophilia ( P =0.02). The FISH score correlated with the total QoL score in both patients with hemophilia and JIA ( r =0.39, P =0.03 and r =0.48, P =0.04, respectively). Conclusions: Although no difference was evident between the patient groups in terms of clinical parameters associated with arthropathy, JIA patients coped better with illness than those with hemophilia. JIA patients had a higher proportion of literate mothers than hemophilia patients; this may affect a patient's ability to cope with issues relating to chronic illness. Implementation of an educational program for mothers of hemophilia patients, during follow-up, may improve the patient's QoL. Also, hemophilia patients should be assisted to improve their QoL in the dimensions of self-esteem and schooling. Lastly, the evaluation of functional disability by FISH in hemophilia patients is important because the FISH score correlated with the total QoL score, as revealed by KINDL. In JIA patients also, functional disabilities caused by arthropathy affected the QoL.